Sentiment Analysis of User Satisfaction Towards Sales Promotion of Gojek Application Service Using Support Vector Machine (SVM) - Haryani, Calandra Alencia; Widjaja, Andree E.; Hery, Hery; Ferdinand, Ferry Vincenttius (ULTIMA InfoSys, 2023)
Customer satisfaction is a crucial factor for the sustainability of a company, including tech companies like Gojek. This condition exists because customer satisfaction affects the continuation of customers purchasing or reusing the company's services. Promotions or offers are commonly applied strategies by companies to enhance attractiveness among competitors and improve customer satisfaction. Therefore, this research aims to understand customer sentiments towards promotions or offers provided by the Gojek company to develop better promotional strategies by increasing customer satisfaction. The data source for this research comes from user tweets on the social media platform Twitter which has now changed to "X". The method used to determine the sentiment of this data is the support vector machine.